Abrasive wear behaviour of sintered composite austenitic stainless steels having ?-Fe and M23C6 phases - Korkut, M. H.; Koc, V.; Gok, M. S. (Taylor & Francis Ltd, 2007)
Using powder metallurgy, composites of austenitic stainless steel were produced along with unreinforced stainless steel mixed with titanium, cobalt and molybdenum particles. Wear resistance of the materials was measured by a two body pin on disc wear tester. SiC abrasive papers of 80 and 220 mesh sizes were used as abrasive media. Wear tests were performed under loads of 10, 20 and 30 N at room temperature. The abrasive wear measurements showed that the softer, unreinforced austenitic stainless steel exhibited higher mass loss than the composites. Furthermore, the abrasive wear resistance of the reinforced austenitic stainless steel composites increased with increasing FeTi, FeMo, or Co volume content. In addition, the wear rate against the 80 grade SiC abrasive paper increased more than against the 220 grade SiC abrasive paper.
Keywords: Powder metallurgy; Wear; Ferrotitanium; Austenitic stainless steels